FISHERIES OF VELLAR ESTUARY PORTO NOVO - Natarajan, P; Devadoss, P; Muniyandi, K (Indian Journal of Fisheries, 2011)
Results of a study of the fishery of fin fishes and shell fishes in the estuaryof Vellar at Porto Novo (11Â° 29' N; 79Â° 46' E) for the period from December1973 to Novemiber 1974 are reported. Several methods of fishing employed in thisestuary are diiscussed. Among fin fishes, as a single group mullets (Mugil spp.)form the major fishery. The topography of the estuary, fluctuations of th6 fishery,and tb; major influence of land drainage due to rain during November and Decemberon the fishery are also discussed. It is estimated that 1,70,000 kg. of fishesand orustacearis are landied annually. The clam wealth of Vellar is one of thebest in Tamil Nadu and about 2,10,000 kg. of clams are estimated to be handpickedannually.